A prospective STudy using invAsive haemodynamic measurements foLLowing catheter ablation for AF and early HFpEF: STALL AF‐HFpEF. (8th March 2021) - Sugumar, Hariharan; Nanayakkara, Shane; Vizi, Donna; Wright, Leah; Chieng, David; Leet, Angeline; Mariani, Justin A.; Voskoboinik, Aleksandr; Prabhu, Sandeep; Taylor, Andrew J.; Kalman, Jonathan M.; Kistler, Peter M.; et al.
Abstract: Aims: The impact of atrial fibrillation (AF) ablation in early heart failure with preserved ejection fraction (HFpEF) is unknown. Our aim was to determine the impact of AF ablation on symptoms and exercise haemodynamic parameters of early HFpEF. Methods and results: Symptomatic AF patients referred for index AF ablation with ejection fraction ≥50% underwent baseline quality of life questionnaires, echocardiography, cardiac magnetic resonance imaging, exercise right heart catheterisation (exRHC), and brain natriuretic peptide (BNP) testing. HFpEF was defined by resting pulmonary capillary wedge pressure (PCWP) ≥15 mmHg or peak exercise PCWP ≥25 mmHg. Patients with HFpEF were offered AF ablation and follow‐up exRHC ≥6 months post‐ablation. Of 54 patients undergoing baseline evaluation, 35 (65%) had HFpEF identified by exRHC. HFpEF patients were older (64 ± 10 vs. 54 ± 13 years, P  < 0.01), and more frequently female (54% vs. 16%, P  < 0.01), hypertensive (63% vs. 16%, P  < 0.001), and suffering persistent AF (66% vs. 11%, P  < 0.001), compared to those without HFpEF. Twenty HFpEF patients underwent AF ablation and follow‐up exRHC 12 ± 6 months post‐ablation. Nine (45%) patients no longer fulfilled exRHC criteria for HFpEF at follow‐up. Patients remaining arrhythmia free ( n  = 9, 45%) showed significant improvements in peak exercise PCWP (29 ± 4 to 23 ± 2 mmHg, P  < 0.01) and Minnesota Living with Heart Failure (MLHF) score (55 ± 30 to 22 ± 30, P  < 0.01) while the remainder did not (PCWP 31 ± 5 to 30.0 ± 4 mmHg, P  = NS; MLHF score 55 ± 23 to 25 ± 20, P  = NS). Conclusion: Heart failure with preserved ejection fraction frequently coexists in patients with symptomatic AF and preserved ejection fraction. Restoration and maintenance of sinus rhythm in patients with comorbid AF and HFpEF improves haemodynamic parameters, BNP and symptoms associated with HFpEF. Abstract : Overview of the study illustrating the proportion of patients referred for consideration of atrial fibrillation (AF) ablation who met the criteria for heart failure with preserved ejection fraction (HFpEF) in panel A . Three‐dimensional reconstruction of the left atrium with radiofrequency lesions used to achieved pulmonary vein electrical isolation at the time of AF ablation in panel B and results of the follow‐up exercise right heart catheterisation at ≥6 months following AF ablation based on arrhythmia recurrence status in panel C . Panel D illustrates the potential interaction between AF and HFpEF. BNP, brain natriuretic peptide; LA, left atrial; LAPW, left atrial posterior wall; LIPV, left inferior pulmonary vein; LSPV, left superior pulmonary vein; PCWP, pulmonary capillary wedge pressure; QoL, quality of life; RIPV, right inferior pulmonary vein; RSPV, right superior pulmonary vein.